2013
DOI: 10.2214/ajr.12.9928
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary CT Angiography as First-Line Imaging for PE: Image Quality and Radiation Dose Considerations

Abstract: Pulmonary CTA plays a vital role in imaging PE. Using dose reduction technologies can provide high-quality diagnostic imaging with a significant reduction in patient dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 57 publications
(65 reference statements)
1
48
0
2
Order By: Relevance
“…High sensitivity (83-100 %) and high specificity (89-98 %) have been reported for routine CTPA for diagnosing pulmonary embolism (PE) [23][24][25]. However, because of the relatively low prevalence (9-35 %) of PE among patients evaluated by CTPA, one must be extremely cautious with the dose delivered to patients [8,26,27], as it has been estimated that 5 fatalities per 100,000 persons per mSv could be expected [28].…”
Section: Discussionmentioning
confidence: 99%
“…High sensitivity (83-100 %) and high specificity (89-98 %) have been reported for routine CTPA for diagnosing pulmonary embolism (PE) [23][24][25]. However, because of the relatively low prevalence (9-35 %) of PE among patients evaluated by CTPA, one must be extremely cautious with the dose delivered to patients [8,26,27], as it has been estimated that 5 fatalities per 100,000 persons per mSv could be expected [28].…”
Section: Discussionmentioning
confidence: 99%
“…Antra, tiriant pacientą, reikėtų išlaikyti tyrimų eiliš-kumą, t. y. esant galimybei, pasirinkti JS nenaudojančius tyrimus (ultragarsinius, magnetinio rezonanso tomografiją) ar pradėti nuo mažesnę apšvitą sukeliančių tyrimų, o sprendimus dėl didesnės apšvitos procedūrų priimti tik įvertinus ankstesnių tyrimų duomenis Trečias apšvitos mažinimo kelias tiesiogiai ir, ko gero, labiausiai priklauso nuo radiologų ir radiologijos technologų kompetencijos, kadangi atliekant rentgeno diagnostines procedūras apšvitos dozę galima reikšmingai sumažinti optimizuojant tyrimų protokolus [30,[45][46][47][48][49]. Kadangi didžiausią diagnostinę apšvitą ir su ja susijusią riziką sąlygoja KT tyrimai, išsamiau aptarsime šių tyrimų dozės mažinimo principus.…”
Section: Medicininės Apšvitos Mažinimasunclassified
“…Jis pasirenkamas pagal keliamus klinikinius uždavinius, pavyzdžiui, krūtinės ląstos srities KT tyrimas įtariant PATE, intersticinę plaučių ligą ar vertinant plaučių vėžio išplitimą reikšmingai skiriasi [49,50,51]. Tyrimo protokolas numato tyrimo apimtį, pasirenkami techniniai skenavimo parametrai, nusprendžiama, ar reikės specialaus paciento paruošimo, intraveninio, peroralinio ar kt.…”
Section: Medicininės Apšvitos Mažinimasunclassified
“…Estrada-Martin and Oldham developed surveys to determine different opinions among radiologists towards the use of CTPA for the diagnosis of PE, and their results showed that most radiologists chose CTPA as the gold standard to diagnose PE [3]. The agreement with this statement is now based on the evidence available in many studies showing that high diagnostic accuracy has been achieved with CTPA in detecting thrombus in both main and side pulmonary artery branches due to rapid technological developments in CT scanning techniques [4][5][6][7][8][9][10][11]. Another important advantage of CT angiography lies in its ability of examining other structures in the thoracic CT scans in addition to the detection of PE, such as assessment of aortic disease and coronary artery disease which is referred to as triple rule-out protocol due to similar symptoms of chest pain presented by these diseases to the emergency department [12,13].…”
Section: Introductionmentioning
confidence: 99%